Monitoring the Diameter Changes of Flax Fibre Elements during Twin Screw Extrusion Using X-Ray Computed Micro-Tomography - Seif Eddine Hamdi; Christine Delisée; Jérome Malvestio; Johnny Beaugrand; Françoise Berzin (Journal of Natural Fibers, 2020)
Fiber size aspect ratio is known to impact the mechanical and reinforcement properties of natural fiber-based composites. However, the representation of fiber diameter change occurring during the extrusion process is controversial compared to the length. Fiber elements undergo multidirectional stresses and complex interactions within the extruder, leading to their breakage, which consequently may modulate their reinforcing properties. To better understand these mechanisms, short fiber reinforced polymer composites were prepared from flax fibers and polypropylene matrix (PP) by melt mixing. Five sampling zones were selected along the screws, both in screw conveying elements and inside blocks of kneading discs. X-ray computed micro-tomography, and 3D images analysis were then used for monitoring sample diameter distributions along the screw profile, according to specific twin-screw compounding conditions. The effects of the considered processing condition on fiber bundle diameters decrease along the screw profile are quantified.